Preparation of Intermediates for Organic Synthsis - Elazar, Meyer (Technium BioChemMed, 2023)
Several synthetic methods are described for the preparation of compounds such as derivatives of natural amino acids, unnatural amino acids, amino esters, oxime esters and amino amides that may serve as intermediates in the synthesis of active pharmaceutical ingredients (APIs) or drugs. The compounds described herein are produced in high yield and purity and the synthetic procedures are detailed along with the NMR spectra of the compounds and useful chemical data relating to these compounds.